Implementasi Model SAVI untuk Mengembangkan Keterampilan Berpikir Kritis Siswa MTs Magetan - Novitasari, Alvy; Soraya, Siti Zazak; Haq, Ahmad Dliyaul; Mufidah, Nastiti (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2025)
This study aims to analyze the application of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model in improving students' critical thinking skills in social studies at MTs Bani Ali Mursyad Magetan. This study is descriptive and qualitative with a case study approach. Primary data were obtained through interviews with the principal, vice principal, teachers, and student representatives, as well as observations of learning activities in the classroom. Secondary data were obtained from school documents such as lesson plans, student worksheets, and learning outcome scores. Data collection techniques included observation, semi-structured interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldana through the stages of data collection, condensation, presentation, and conclusion drawing with source triangulation and member check for validity. The results showed that the application of the SAVI model improved students' critical thinking skills, particularly in the intellectual aspect, which trained their ability to analyze, evaluate, and conclude logically through discussions and case studies. However, the auditory aspect is still less than optimal due to limitations in media and internet networks. In addition, there are several supporting and inhibiting aspects of SAVI for critical thinking skills. Nevertheless, overall, the implications of the SAVI model are effective in creating interactive learning that supports the development of students' critical thinking skills in madrasahs.